Prospective follow-up in various subtypes of cardiomyopathies: insights from the ESC EORP Cardiomyopathy Registry - Gimeno, Juan R; Elliott, Perry M; Tavazzi, Luigi; Tendera, Michal; Kaski, Juan P; Laroche, Cecile; Barriales-Villa, Roberto; Seferovic, Petar; Biagini, Elena; Arbustini, Eloisa; Lopes, Luis R; Linhart, Ales; et al. (European heart journal. Quality of care & clinical outcomes, 2021)
AIMS: The European Society of Cardiology (ESC) European Observational Research Programme (EORP) Cardiomyopathy Registry is a prospective multinational registry of consecutive patients with cardiomyopathies. The objective of this report is to describe the short-term outcomes of adult patients (≥18 years old). METHODS AND RESULTS: Out of 3208 patients recruited, follow-up data at 1 year were obtained in 2713 patients (84.6%) [1420 with hypertrophic (HCM); 1105 dilated (DCM); 128 arrhythmogenic right ventricular (ARVC); and 60 restrictive (RCM) cardiomyopathies]. Improvement of symptoms (dyspnoea, chest pain, and palpitations) was globally observed over time (P < 0.05 for each). Additional invasive procedures were performed: prophylactic implantation of implantable cardioverter-defibrillator (ICD) (5.2%), pacemaker (1.2%), heart transplant (1.1%), ablation for atrial or ventricular arrhythmia (0.5% and 0.1%). Patients with atrial fibrillation increased from 28.7% to 32.2% of the cohort. Ventricular arrhythmias (VF/ventricular tachycardias) in ICD carriers (primary prevention) at 1 year were more frequent in ARVC, then in DCM, HCM, and RCM (10.3%, 8.2%, 7.5%, and 0%, respectively). Major cardiovascular events (MACE) occurred in 29.3% of RCM, 10.5% of DCM, 5.3% of HCM, and 3.9% of ARVC (P < 0.001). MACE were more frequent in index patients compared to relatives (10.8% vs. 4.4%, P < 0.001), more frequent in East Europe centres (13.1%) and least common in South Europe (5.3%) (P < 0.001). Subtype of cardiomyopathy, geographical region, and proband were predictors of MACE on multivariable analysis. CONCLUSIONS: Despite symptomatic improvement, patients with cardiomyopathies remain prone to major clinical events in the short term. Outcomes were different not only according to cardiomyopathy subtypes but also in relatives vs. index patients, and according to European regions.
Keywords: kardiologie; MACE; Cardiomyopathies; Adolescent; následné studie; Cardiology; Adult; Prospective Studies; dospělí; Cardiomyopathy; registrace; kardiomyopatie; mladiství; Follow-Up Studies; Atrial Fibrillation; lidé; Humans; Registry; Prognosis; Registries; fibrilace síní; prospektivní studie